A versatile and automated microfluidic platform for a quantitative magnetic bead based protocol: application to gluten detection. Issue 17 (9th June 2022) - Parent, Charlotte; Laurent, Patricia; Goujon, Charles-Elie; Mermet, Xavier; Keiser, Armelle; Boizot, François; Charles, Raymond; Audebert, Lucas; Fouillet, Yves; Cubizolles, Myriam
Abstract : We present an automated microfluidic platform using a hyperelastic membrane for quantitative magnetic bead based protocol integration. Abstract : A microfluidic platform for the integration of multi-step biological assays has been developed. The presented system is a unique instrument compatible with microfluidic chips for various applications based on bead manipulation. Two examples of microfluidic cartridges are presented here. The first one contains two rows of eight chambers (40 and 80 μL), six reagent inlets, eight testing solution (calibrators and samples) inlets and eight outlets to reproduce precisely each step of a biological assay. This configuration is versatile enough to integrate many different biological assays and save a lot of development time. The second architecture is dedicated to one specific protocol and is completely automated from the standard and sample dilutions to the optical detection. Linear dilutions have been integrated to prepare automatically a range of standard concentrations and outlets have been modified for integrated colorimetric detection. The technology uses pneumatically collapsible chambers to perform all the fluidic operations for a fully automated protocol such as volume calibrations, fluid transport, mixing, and washing steps. A programmable instrument with a software interface has been developed to adapt rapidly a protocol to this cartridge. As an example, these new microfluidic cartridges have been used to successfully perform an immunoassay for gluten detection in the dynamic range of 10–30 ppm with good sensitivity (2 ppm) and specificity.